Project Report on Designing Signal using Data Acquisition Card for Personal Computer - ANAND S, SARAVANAN R M, RADHAKRISHNAN M and VENKATARAMAN (1999)
INTERNAL GUIDE:R BABU, MVJCE
Keywords: Designing Signal using Data Acquisition Card for Personal Computer